1996
DOI: 10.1021/ma9602886
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of the Behavior of a Reactive Epoxy−Amine System by Means of Dynamic Rheology. 2. High-Tg Epoxy−Amine System

Abstract: A high-T g epoxy−amine system based on diglycidyl ether of bisphenol A (DGEBA) and 4,4‘-methylenebis[3-chloro-2,6-diethylaniline] (MCDEA) was studied near the gel point in isothermal conditions from 80 to 180 °C by means of a rheological method, thus, below and above the glass transition temperature of the fully cured network, T g ∞ (T g ∞ = 177 °C). The lower limit of this temperature range is close to gel T g (gel T g = 50 °C), the temperature at which gelation and vitrification occur simultaneously. Close t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
66
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 30 publications
12
66
0
1
Order By: Relevance
“…It is observed that the agreement between experimental results and model calculations is good for the three epoxy-amine systems. Table II contains our values of rate constants, K 0 and K 1 , and of the times of gelation, t gel (gelation occurs at conversion 0.59 for DGEBA/ MCDEA and DGEBA/MDEA 20 and conversion about 0.6 for DGEBA/DDS 19 ). Also reported are the values of these parameters calculated using Arrhenius laws found by Girard-Reydet et al 19 The two sets of values are close.…”
Section: ©Ch©ch¤ + ©Nh¤mentioning
confidence: 99%
“…It is observed that the agreement between experimental results and model calculations is good for the three epoxy-amine systems. Table II contains our values of rate constants, K 0 and K 1 , and of the times of gelation, t gel (gelation occurs at conversion 0.59 for DGEBA/ MCDEA and DGEBA/MDEA 20 and conversion about 0.6 for DGEBA/DDS 19 ). Also reported are the values of these parameters calculated using Arrhenius laws found by Girard-Reydet et al 19 The two sets of values are close.…”
Section: ©Ch©ch¤ + ©Nh¤mentioning
confidence: 99%
“…The diffusion coefficient (D) results from the competition between the driving force (which is the thermal motion, k B ÁT) and the friction term (f) which is dependent on the nature of the particle environment [22][23][24][25]. D is considered constant with time for a steady environment.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…So, the curing temperature variation leads to 2 opposite effects and, in order to predict their influence onto the total diffusion (Q) it was necessary to develop Eq. (7) as a function of T [25][26][27]:…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Therefore, vitrification should be surpassed in order to get complete cure by increasing the curing temperature above the T g of the fully cured material. Rheometric monitoring of curing processes is a methodology used to determine accurately the gel point and vitrification because it is highly sensitive to the dramatic changes in the viscoelastic properties that occur [32,33,34].…”
Section: Rheological Studies Of the Curing Of The Formulationsmentioning
confidence: 99%